Libertarian Legal Theory in the Stream of the History of the Philosophy of Law - Vagharshyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2018)
In the turbulent flow of political and legal doctrines of the new and modern era, V. Nersеsiantz`s libertarian-legal theory has its unique and not yet fully acknowledged place. The mentioned theory by its universalism, depth, concept of civil society and property competes with the doctrines of G. Hegel and K. Marx , putting forward an alternative way of the world socio-political and legal development. This doctrine is also very relevant to the reality of the Republic of Armenia and it can contribute to the solution of national political, economic, social, human, constitutional-legal and other serious problems.
Keywords: type of state and law, end of history, natural law, civilism, post-capitalism, post-socialism, legal axiology